Asynchronous recovery of hydrolytic and oxidative enzymes during wetland restoration - Xiangling Zhou; Ting Wang; Lifei Su; Siqi Zheng; Shijia Liu; Yi Liu; Wenhui Quan; Tingting Hu; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; et al. (Agriculture, Ecosystems & Environment, 2026)

Cooperative detoxification through GSTm1 and GSTs2 reveals distinct transcription factors BH1 and zen2 in dinotefuran resistance in Nilaparvata lugens - Bingjie Tang; Yutao Hu; Bin Liu; Xin Lei; Pingping Guo; Jiahui Liu; Wenqing Zhang (Pesticide Biochemistry and Physiology, 2026)

Multi-omics analysis of the rhizosphere effects and molecular mechanisms of Ageratum conyzoides linn. at different stages of Cd, Pb, and Zn co-stress - Yuexin Fu; Mouyixing Chen; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu; Shaohong You (Journal of Environmental Management, 2026)

Tumor microenvironment-programmed dual-responsive nanoprobes enable fluorescence/photoacoustic imaging-guided enhanced tumor phototherapy by blocking protective autophagy - Jie Zhao; Haiyi Zhang; Juan Lu; Min Fan; Pingping Jie; Zhengzhen Yuan; Yingying Qi; Qin Zhang; Jian Shu; Yongcan Guo; Zhijin Fan; Lei Zhang (Chemical Engineering Journal, 2026)

An improved landslide early warning and forecasting method based on multi-component ground-based radar data - Pingping Huang; Xingyan Guo; Weixian Tan; Hui Wu; Yaolong Qi; Wei Xu; Yongguang Zhai (Bulletin of Engineering Geology and the Environment, 2026)

Restoring aquaculture ponds to coastal wetlands using native vegetation reduces methane (CH4) production and emissions - Wenjing Liu; Hong Yang; Ping Yang; Qitao Xiao; Jujuan Gao; Lihua Wang; Chuan Tong; Yingzi Wang; Pingping Guo; Dongyao Sun; Yongxin Lin; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Identification of a putative novel carlavirus infecting Gynura bicolor in China - Lei Xu; Mengze Guo; Pingping Sun; Lei Zhang; Zhengnan Li (Archives of Virology, 2026)

A spatial ZVI strategy boosts digestion performance and ammonium recovery through in-situ conductive mineral formation - Yuqi Gong; Xiaocheng Guo; Pingping Huang; Yangzhao Guo; Yikun Jiang; Fengzhi Jiang; Zhigang Ma; Siping Ji (Journal of Water Process Engineering, 2026)

Large spatiotemporal variability in CH4 emissions from a subtropical coastal creek in southeast China affected by hydrological and biogeochemical processes - Lihua Wang; Ping Yang; Yingzi Wang; Pingping Guo; Derrick Y.F. Lai; Kwok Pan Chun; Chuan Tong; Dongyao Sun; Jiafang Huang; Guanpeng Chen; Hong Yang (Journal of Hydrology, 2026)

Reshaping metal composition and sources to reduce PM2.5 oxidative potential by clean energy policies in Xi'an, China - Lijing Zhang; Pingping Liu; Hongyu Yan; Yuhao Dong; Shaozhong Guo; Hongmei Xu (Atmospheric Environment, 2026)

Microbial transformation and mineral precipitation for Cd-Pb-As co-removal with novel PRB materials - Yepu Li; Yanxin Zhang; Mengwei Li; Pingping Xie; Tongcai Wang; Guobing Wang; Hongyan Guo (Journal of Water Process Engineering, 2026)

Hydrological response to climate change and urbanization in a semi-arid urban river - Jiqiang Lyu; Yan Wang; Kexin Wang; Wenya Liu; Dongyong Sun; Pingping Luo; Zhaohui Zhou; Meng Jiao; Aidi Huo; Peng Guo (Urban Climate, 2025)

Hydrolase-oxidase responses mediate distinct carbon dynamics following wetland conversion to paddy versus upland systems - Lifei Su; Yi Liu; Lishan Tan; Xiangling Zhou; Ting Wang; Yinyin She; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; Min Luo (Soil Biology and Biochemistry, 2025)

Long-term monitoring reveals scale-dependent decoupling of waterbird diversity at a tropical island flyway node - Miaomiao He; Yufeng Lin; Cheng Cheng; Zhiqin Zhou; Pingping Guo; Xin Fan; Wenqing Wang (Journal of Environmental Management, 2025)

Synergistic molecular design strategy for near-infrared multi-resonance emitters with accelerated spin-flip - Weibo Cui; Yexuan Pu; Linjie Li; Lixiao Guo; Pingping Zheng; Yun Geng; Chenglong Li (Chemical Engineering Journal, 2025)

Deciphering spatial pattern and environmental drivers of deep soil moisture security: insights from integrating spatial non-stationarity in large-scale analysis - Yongping Tong; Yunqiang Wang; Zimin Li; Pingping Zhang; Wei Hu; Jingxiong Zhou; Xiangyu Guo; Hui Sun; Alexis Comber; Ronny Lauerwald (CATENA, 2025)

Characteristics and risk assessment of heavy metals and their acid-extractable fractions in atmospheric dustfall in urban and rural areas of Xi’an, China - Hao Zhang; Pingping Liu; Lijing Zhang; Shaozhong Guo; Hongyu Yan; Zhiwei Xue; Hongmei Xu; Zhenxing Shen (Air Quality, Atmosphere & Health, 2025)

The effect of autophagy activation on apoptosis and myofibrillar structural proteins during the post-mortem storage of Esox lucius - Xuemei Fan; Yibo Liu; Xin Guo; Yabo Wei; Pingping Liu; Hui Li; Xin Chen; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2025)

Integrative Single-Cell Analysis Decodes Gene Expression and Chromatin Accessibility in the Developing Human Fetal Brain - Tiantian Xu; Huihui Tao; Lingling Zhou; Haiyan Yu; Shi Bai; Hui Guo; Zhipeng Zeng; Wei Shi; Chunmei Wen; Mengyao Wu; Xuejia Zheng; Pingping Ye; et al. (Molecular Neurobiology, 2025)

Retrieving soil heavy metal concentrations using hyperspectral remote sensing images based on three-band indices at a coal mine in China - Haorui Bai; Bin Guo; Lin Pei; Bo Zhang; Pingping Luo; Tengyue Guo; Min Wu; Xiaohan Ma (Advances in Space Research, 2025)

Coastal creeks as greenhouse gas hotspots: the role of nutrient availability and microbial activity - Guanpeng Chen; Jianuo Gao; Ping Yang; Wenjing Liu; Dongyao Sun; Yongxin Lin; Chuan Tong; Wenjing Tan; Pingping Guo; Hong Yang (Journal of Hydrology, 2025)

Expanding scales: Achieving prediction of van Genuchten model hydraulic parameters in deep profiles by incorporating broad in situ soil information in pedotransfer functions - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Xiangyu Guo; Ting Wang; Yuting Xu; Hui Sun; Pingping Zhang; Zimin Li; Ronny Lauerwald (Journal of Hydrology, 2025)

Unexpectedly stable soil organic carbon in tidal marshes under combined nitrogen loading and increased inundation compared to individual effects - Tianning Fan; Jiafang Huang; Guopeng Liang; Shengen Liu; Dehong Hu; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo; Chuan Tong (Limnology and Oceanography, 2025)
Tidal marshes serve as critical carbon (C) sinks, yet face increasing threats from global environmental changes. While previous research has documented how nitrogen (N) loading and sea‐level rise affect total C pools individually, their impacts on soil organic carbon (SOC) stabilization remain critically underexplored, particularly when these factors co‐occur in tidal marsh ecosystems. Through a 3‐yr field experiment, we analyzed how these factors, alone and combined, impact SOC stabilization by examining SOC fraction dynamics. Results showed that N loading increased particulate organic carbon (POC) by 18% and decreased mineral‐associated organic carbon (MAOC) by 13%, reducing SOC stabilization. Conversely, increased inundation raised MAOC by 31% and decreased POC by 19%, promoting SOC stabilization. The decreased MAOC under N loading stemmed from reduced fungal necromass C, while the increased POC related to lower phenol oxidase activity. In contrast, with increased inundation, MAOC rose due to iron‐bound organic C (Fe‐OC) accumulation, while POC declined from increased phenol oxidase activity. When both factors were applied together, SOC stabilization remained at control levels. This occurred because the combined effect maintained oxidative enzyme activities and thus retained POC levels. The simultaneous reduction in fungal necromass C and enhancement of Fe‐OC associations established complementary mechanisms that maintained MAOC at levels equivalent to control. Our findings reveal that N loading and increased inundation drive contrasting patterns of SOC stabilization, while their combination produces uniquely stabilized C dynamics. This insight challenges single‐factor predictions and underscores the importance of multi‐factor experiments in understanding ecosystem responses under concurrent global change scenarios.

Divergence of microbial carbon use efficiency and soil organic carbon along a tidal flooding gradient in a subtropical coastal wetland - Ji Tan; Jiafang Huang; Wenhui Quan; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo (Water Research, 2025)

Dual signal output detection of acetamiprid residues in medicine and food homology products via nanopore biosensor - Yao Li; Jiyuan Tu; Hong Wang; Kexin Luo; Pingping Xiao; Tangbin Liao; Guo-Jun Zhang; Zhongyue Sun (Food Chemistry, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Complete genome sequence and genome organization of Ficus pumila-associated virus, a new putative member of the family Tymoviridae - Mengze Guo; Pingping Sun; Xudong Fan; Jianwei Guo; Lei Zhang; Zhengnan Li (Archives of Virology, 2025)

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

Divergent invasive and native wetland plant microbial community responses to estuarine wetland salinity gradients - Zongsheng Yuan; Huanhuan Rao; Ziwen Ren; Hao Xue; Yingzi Wang; PingPing Guo; Yongji Huang; Yange Zhang; Zonghua Wang; Songbiao Chen; Yingjiao Zhang (CATENA, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Study on the Improvement of Coastal Pumping Station Inlet Flow Regime and Evaluation of Transverse Flow Velocity Elimination - Fusheng Lv; Pingping Li; Bo Zhu; Xilong Guo; Lei Wang; Lei Xu (Journal of Marine Science and Engineering, 2025)
Pump station engineering is extensively utilized in water supply and drainage, as well as agricultural irrigation. Due to its geographical advantages and significant comprehensive benefits, the construction of pumping stations in coastal areas has gained substantial attention in recent years. Adverse flow conditions caused by various factors negatively affect the inlet flow regime of pumps, becoming a key factor that restricts the operating life and further development of pump station systems. Optimizing the flow regime in the forebay is crucial for enhancing overall engineering quality, minimizing pump performance degradation, and reducing the risks of cavitation and vibration. This study investigates the flow characteristics of the forebay by combining the Navier–Stokes equations and the k−ε RNG turbulence model. The analysis focuses on the internal flow field, transverse flow before the inlet channel, and the uniformity of flow velocity distribution after the inlet channel. Numerical simulations are validated through physical model tests. We examine the flow characteristics in the forebay, analyze the causes of internal flow disorder, and propose a reasonable and practical rectification scheme for the forebay. Additionally, we elucidate the mechanism of flow state optimization through partition walls. The findings indicate that with the optimal partition wall length, the average elimination rate of transverse flow velocity before the pump station inlet channel reached 48.3%, and the uniformity of flow velocity distribution after the inlet increased by 3.24%. These research findings contribute to mitigating cavitation and vibration in water pump units, providing theoretical support for the safe operation of coastal pumping stations.

Influence of topography on the fragmentation and mobility of landslides - Zhaodong Li; Jian Guo; Tonglu Li; Ping Li; Xuetong Ma; Mengmeng Zhang; Enxian Jia; Pingping Xu (Bulletin of Engineering Geology and the Environment, 2025)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Pioneer plants promote soil formation in a mixture of bauxite tailings and red mud - Xusheng Jiang; Mengting Lin; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu (Journal of Environmental Management, 2024)

Metagenomic and isotopic insights into carbon fixation by autotrophic microorganisms in a petroleum hydrocarbon impacted red clay aquifer - Zhuo Ning; Yizhi Sheng; Shuang Gan; Caijuan Guo; Shuaiwei Wang; Pingping Cai; Min Zhang (Environmental Pollution, 2024)

Heavy metals and bacterial community determine resistance genes distribution in agricultural soils surrounding long-term mining area - Pingping Wu; Jing Wang; Zhibin Guo; Yihan Cheng; Ji Wu (Applied Soil Ecology, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Activation of peracetic acid by electrodes using biogenic electrons: A novel energy- and catalyst-free process to eliminate pharmaceuticals - Rusen Zou; Wenqiang Yang; Babak Rezaei; Kai Tang; Kuangxin Guo; Pingping Zhang; Stephan Sylvest Keller; Henrik Rasmus Andersen; Yifeng Zhang (Water Research, 2024)

Coastal conversion alters topsoil carbon, nitrogen and phosphorus stocks and stoichiometric balances in subtropical coastal wetlands - Minjie Hu; Jingtao Wang; Jordi Sardans; Hui Wu; Ranxu Ni; Pingping Guo; Ruibing Yan; Haoyu Liao; Chunya Liu; Josep Peñuelas; Chuan Tong (Science of The Total Environment, 2024)

Non-intrusive load monitoring based on MoCo_v2, time series self-supervised learning - Tie Chen; Jiaqi Gao; Yimin Yuan; Shinan Guo; Pingping Yang (Energy and Buildings, 2024)

Development of a facile one-pot synthesized fluorescent green polyesters as cooling water antiscalants for industrial application - Lijun Gao; Tianming Gao; Jiuying Feng; Shaohong Mo; Yanbei Guo; Pingping Guo; Shiyun Pan; Yuqing Cheng; Qian Yang (Desalination, 2024)

Corrigendum to “Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus” [Veterin. Microbiol. 276 (2023) 109615] - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

Rotation of Celosia argentea and Sedum plumbizincicola promotes Cd phytoextraction efficiency - Jie Liu; Xusheng Jiang; Xuehong Zhang; Pingping Jiang; Guo Yu (Journal of Hazardous Materials, 2024)

An integrated simulation-optimization approach for combined allocation of water quantity and quality under multiple uncertainties - Yaping Huang; Yanpeng Cai; Chao Dai; Yanhu He; Hang Wan; Hongjiang Guo; Pingping Zhang (Journal of Environmental Management, 2024)

Identification of a novel waikavirus infecting Pittosporum tobira in China - Mengze Guo; Lei Zhang; Xudong Fan; Pingping Sun; Jianwei Guo; Zhengnan Li (Archives of Virology, 2024)

miR397 regulates cadmium stress response by coordinating lignin polymerization in the root exodermis in Kandelia obovata - Chenglang Pan; Mingxiong Zhang; Jianming Chen; Haoliang Lu; Xuemei Zhao; Xiaofeng Chen; Lu Wang; Pingping Guo; Shuyu Liu (Journal of Hazardous Materials, 2024)

Effect of apple high-methoxyl pectin on heat-induced gelation of silver carp myofibrillar protein - Han Yu; Yunfeng Zhao; Runze Li; Xin Guo; Pingping Liu; Jian Zhang (Food Chemistry, 2024)

Identification and functional analysis of a CbSHR homolog in controlling adventitious root development in Catalpa bungei - Ziyuan Hao; Jingyi Liu; Yao Teng; Xinchang Wang; Peiyao Jiang; Weijie Si; Hongying Li; Fuqiang Yang; Pingping Guo; Jiawen Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Physiological and biochemical responses of Leersia hexandra Swartz to nickel stress: Insights into antioxidant defense mechanisms and metal detoxification strategies - Mouyixing Chen; Pingping Jiang; Xuehong Zhang; Geoffrey I. Sunahara; Jie Liu; Guo Yu (Journal of Hazardous Materials, 2024)

Preparation and properties of films loaded with cellulose nanocrystals stabilized Thymus vulgaris essential oil Pickering emulsion based on modified tapioca starch/polyvinyl alcohol - Xin Guo; Xiaorui Wang; Yabo Wei; Pingping Liu; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2024)

Changing soil available substrate primarily caused by fertilization management contributed more to soil respiration temperature sensitivity than microbial community thermal adaptation - Zhibin Guo; Chang-An Liu; Keke Hua; Daozhong Wang; Pingping Wu; Shuixia Wan; Chuanlong He; Linchuan Zhan; Ji Wu (Science of The Total Environment, 2024)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Increase in iron-bound organic carbon content under simulated sea-level rise: A “marsh organ” field experiment - Dehong Hu; Wenjing Lan; Min Luo; Tianning Fan; Xin Chen; Ji Tan; Shihua Li; Pingping Guo; Jiafang Huang (Soil Biology and Biochemistry, 2023)

Rasterizing CO2 emissions and characterizing their trends via an enhanced population-light index at multiple scales in China during 2013–2019 - Bin Guo; Tingting Xie; Wencai Zhang; Haojie Wu; Dingming Zhang; Xiaowei Zhu; Xuying Ma; Min Wu; Pingping Luo (Science of The Total Environment, 2023)

Exploring the association between air pollution and Parkinson’s disease or Alzheimer’s disease: a Mendelian randomization study - Pingping Ning; Xingzhi Guo; Qiumin Qu; Rui Li (Environmental Science and Pollution Research, 2023)

Quantitative assessment of spatiotemporal dynamics in vegetation NPP, NEP and carbon sink capacity in the Weihe River Basin from 2001 to 2020 - Jiqiang Lyu; Xianghang Fu; Chen Lu; Yueyan Zhang; Pingping Luo; Peng Guo; Aidi Huo; Meimei Zhou (Journal of Cleaner Production, 2023)

Incorporating biotic phosphorus-acquisition strategies into soil phosphorus transformation under long-term salinization in a tidal wetland - Tianning Fan; Min Luo; Ji Tan; Dehong Hu; Xin Chen; Jiafang Huang; Shihua Li; Pingping Guo; Ji Chen (CATENA, 2023)

Bacterial wilt suppressive composts: Significance of rhizosphere microbiome - Jia Ding; Ning Wang; Pingping Liu; Baoju Liu; Yuelin Zhu; Jing Mao; Yue Wang; Xiaoyan Ding; Hefa Yang; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

Fault geometry and low frictional control of the near-field postseismic deformation of the 2021 Mw 7.3 Maduo earthquake - Lei Zhao; Wenbin Xu; Lei Xie; Dezheng Zhao; Zhihui Zhu; Pingping Wu; Huili Guo (Tectonophysics, 2023)

The association between urinary polycyclic aromatic hydrocarbon metabolites and liver function among US population: a cross-sectional study - Manthar Ali Mallah; Zhu Ying; Mukhtiar Ali; Junwei Guo; Feifei Feng; Wei Wang; Pingping Shang; Qiao Zhang (Environmental Geochemistry and Health, 2023)

Long-term application of organic amendments changes heavy metals accumulation in wheat grains by affecting soil chemical properties and wheat yields - Pingping Wu; Zhibin Guo; Keke Hua; Daozhong Wang (Journal of Soils and Sediments, 2023)

Carbon amendment rather than nitrate fertilization dominated the reassembly of the total, denitrifying, and DNRA bacterial community in the anaerobic subsoil - Chen Chen; Pingping Liu; Yingjie Liu; Yuquan Wei; Ji Li; Guo-chun Ding (Journal of Soils and Sediments, 2023)

Changes in bacterial diversity, co-occurrence pattern, and potential pathogens following digestate fertilization: Extending pathogen management to field for anaerobic digestion of livestock manure - Jingyang Gong; Baojun Liu; Pingping Liu; Lina Zhang; Chen Chen; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

Effects of different levels of dietary chlorogenic acid supplementation on growth performance, intestinal integrity, and antioxidant status of broiler chickens at an early age - Wenhan Liu; Pingping Zha; Lili Guo; Yueping Chen; Yanmin Zhou (Animal Feed Science and Technology, 2023)

Integrated transcriptome and metabolome analysis reveals the mechanism of tolerance to manganese and cadmium toxicity in the Mn/Cd hyperaccumulator Celosia argentea Linn - Guo Yu; Habib Ullah; Xinshuai Wang; Jie Liu; Baoliang Chen; Pingping Jiang; Hua Lin; Geoffrey I. Sunahara; Shaohong You; Xuehong Zhang; Asfandyar Shahab (Journal of Hazardous Materials, 2023)

Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2023)

Aquaculture Exacerbates the Accumulation and Ecological Risk of Heavy Metal from Anthropogenic and Natural Sources, a Case Study in Hung-tse Lake, China - Jiping Li; Hao Cui; Yanhui Guo; Pingping Li; Jiangang Han; Wei Li (Water, Air, & Soil Pollution, 2023)

The genome of a mangrove plant, Avicennia marina, provides insights into adaptation to coastal intertidal habitats - Dongna Ma; Qiansu Ding; Zejun Guo; Chaoqun Xu; Pingping Liang; Zhizhu Zhao; Shiwei Song; Hai-Lei Zheng (Planta, 2022)

Breast Cancer Awareness Based on Health Information Literacy and Influential Factors among Female Nursing Students in China - Shu Yang; Ping Li; Lin Yu; Na Liu; Jie Wang; Pingping Guo; Xuehui Zhang; Wei Zhang (Journal of Cancer Education, 2022)

Pathways of cadmium fluxes in the root of the hyperaccumulator Celosia argentea Linn. - Pingping Jiang; Yingyi Zheng; Jie Liu; Guo Yu; Fanyu Lin (Environmental Science and Pollution Research, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Effects of air pollution on physiological traits of Ligustrum lucidum Ait. leaves in Luoyang, China - Xiping Zhao; Pingping Guo; Yongqiang Yang; Haixin Peng (Environmental Monitoring and Assessment, 2021)

Nitrogen addition inhibits total monoterpene emissions in subtropical forest floor of South China - Xingran Huang; Lili Zheng; Pingping Guo; Zhigang Yi (Soil Ecology Letters, 2021)

Characterization on the physiological traits of plants and yield formation capacity upon water- and N-saving conditions in wheat (T. aestivum L.) - Pingping Du; Liguo Guo; Lili Si; Le Han; Shuang Zhang; Fangfang Li; Kai Xiao (Acta Physiologiae Plantarum, 2021)

Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

Spatio-temporal Variation of Water Heat Flux Using MODIS Land Surface Temperature Product over Hulun Lake, China During 2001–2018 - Boyu Zhao; Jia Du; Kaishan Song; Pierre-André Jacinthe; Xiaoyun Xiang; Haohao Zhou; Zhichao Yang; Liyan Zhang; Pingping Guo (Chinese Geographical Science, 2020)

Correction to: B7-H3 modulates endothelial cell angiogenesis through the VEGF cytokine - Huijun Lai; Zhongwen Sun; Jie Yang; Pingping Wu; Yundi Guo; Jing Sun (Immunologic Research, 2020)

Interaction of Mn and Cd during their uptake in Celosia argentea differs between hydroponic and soil systems - Jie Liu; Guo Yu; Pingping Jiang; Xingfeng Zhang; Dejia Meng; Zhe Chen; Alan J. M. Baker; Rongliang Qiu (Plant and Soil, 2020)

Extracellular production of recombinant N-glycosylated anti-VEGFR2 monobody in leaky Escherichia coli strain - Ning Ding; Xin Fu; Yao Ruan; Jing Zhu; Pingping Guo; Lichi Han; Jianing Zhang; Xuejun Hu (Biotechnology Letters, 2019)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

B7-H3 modulates endothelial cell angiogenesis through the VEGF cytokine - Huijun Lai; Zhongwen Sun; Jie Yang; Pingping Wu; Yundi Guo; Jing Sun (Immunologic Research, 2019)

Foliage application of nitrogen has less influence on soil microbial biomass and community composition than soil application of nitrogen - Xingran Huang; Yanfei Liu; Yiyong Li; Pingping Guo; Xiong Fang; Zhigang Yi (Journal of Soils and Sediments, 2019)

Mechanical Testing of Tomato Plant Stem in Relation to Structural Composition - Xiliang Zhang; Qian Guo; Yunfeng Xu; Pingping Li; Cheng Chen; Shuo Wu (Agricultural Research, 2016)

Maternal Thyroxine Levels During Pregnancy and Outcomes of Cognitive Development in Children - Pingping Wang; Jian Gao; Shihua Zhao; Yong Guo; Zengfang Wang; Feng Qi (Molecular Neurobiology, 2016)

Transplantation of mesenchymal stem cells improves type 1 diabetes mellitus - Lisha Li; Furong Li; Feng Gao; Yali Yang; Yuanyuan Liu; Pingping Guo; Yulin Li (Cell and Tissue Research, 2016)

A novel dual EGFR/HER2 inhibitor KU004 induces cell cycle arrest and apoptosis in HER2-overexpressing cancer cells - Chongchong Tian; Pingping Ding; Ziqiao Yuan; Han Li; Yanxia Zhao; Lan Sun; Qingming Guo; Zhenzhong Wang; Lixin Sun; Luyong Zhang; Zhenzhou Jiang (Apoptosis, 2015)

PI3K/Akt/uncoupling protein 2 signaling pathway may be involved in cell senescence and apoptosis induced by angiotensin II in human vascular endothelial cells - Ping Li; Xin Guo; Pingping Lei; Shoujun Shi; Shike Luo; Xiaoshu Cheng (Molecular Biology Reports, 2014)

Soil fertility and its significance to crop productivity and sustainability in typical agroecosystem: a summary of long-term fertilizer experiments in China - Qingyin Shang; Ning Ling; Xumeng Feng; Xiuxia Yang; Pingping Wu; Jianwen Zou; Qirong Shen; Shiwei Guo (Plant and Soil, 2014)

Ammonia volatilization in Chinese double rice-cropping systems: a 3-year field measurement in long-term fertilizer experiments - Qingyin Shang; Cuimin Gao; Xiuxia Yang; Pingping Wu; Ning Ling; Qirong Shen; Shiwei Guo (Biology and Fertility of Soils, 2014)

Slow decomposition and limited nitrogen release by lower order roots in eight Chinese temperate and subtropical trees - Yanmei Xiong; Pingping Fan; Shenglei Fu; Hui Zeng; Dali Guo (Plant and Soil, 2013)

Slow decomposition of lower order roots: a key mechanism of root carbon and nutrient retention in the soil - Pingping Fan; Dali Guo (Oecologia, 2010)

Molecular mechanisms controlling pavement cell shape in Arabidopsis leaves - Pingping Qian; Suiwen Hou; Guangqin Guo (Plant Cell Reports, 2009)